2016
DOI: 10.1177/0333102416665223
|View full text |Cite
|
Sign up to set email alerts
|

Reduced insula habituation associated with amplification of trigeminal brainstem input in migraine

Abstract: Background: Impaired sensory processing in migraine can reflect diminished habituation, increased activation, or even increased gain or amplification of activity from the primary synapse in the brainstem to higher cortical/subcortical brain regions. Methods: We scanned 16 episodic migraine (interictal) and 16 healthy controls (cross-sectional study), and evaluated brain response to innocuous air-puff stimulation over the right forehead in the ophthalmic nerve (V 1 ) trigeminal territory. We further evaluated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 45 publications
6
30
0
Order By: Relevance
“…Previous neuroimaging studies during migraine attacks have repeatedly provided evidence of activation in bilateral insula, which was considered as a non-specific response to pain (2,4,9,10,38). Between attacks, migraineurs also had abnormal insular cortex connectivity (39,40) and habituation in response to repeated sensory stimuli (41,42). In the present study, we show that migraine patients during an attack have greater bilateral insula connectivity with MPFC and right IPL areas of the DMN than healthy volunteers, in the absence of a specific task.…”
Section: Dmn-to-insula Connectivitysupporting
confidence: 55%
“…Previous neuroimaging studies during migraine attacks have repeatedly provided evidence of activation in bilateral insula, which was considered as a non-specific response to pain (2,4,9,10,38). Between attacks, migraineurs also had abnormal insular cortex connectivity (39,40) and habituation in response to repeated sensory stimuli (41,42). In the present study, we show that migraine patients during an attack have greater bilateral insula connectivity with MPFC and right IPL areas of the DMN than healthy volunteers, in the absence of a specific task.…”
Section: Dmn-to-insula Connectivitysupporting
confidence: 55%
“…These comparisons were performed using a two-way ANOVA followed by post-hoc testing (STATA 14, Stata Corporation, College Station, TX). Our previous study [40] found altered trigeminal air-puff processing in MIG, and the current study investigated how eRAVANS affects brainstem response to such trigeminal input.…”
Section: Methodsmentioning
confidence: 94%
“…This index has some advantages over other measurements such as the number of days after or preceding an attack, because it takes into account the variability of attack frequency between patients, normalizing the time since last attack by the total duration of the interictal period. This measurement has been previously shown by our group to correlate with fMRI activation in brainstem trigeminal nuclei in response to ophthalmic nerve somatosensory input [40], and our current analysis explored whether the interictal phase index is also sensitive to brainstem processing of RAVANS stimulation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations